Comprehensive Transcriptome Sequencing Analysis of Hirudinaria manillensis in Different Growth Periods - Shan, Huiquan; Ren, Ke; Liu, Jiasheng; Rehman, Saif ur; Yan, Xiuying; Ma, Xiaocong; Zheng, Yalin; Feng, Tong; Wang, Xiaobo; Li, Zhipeng; Zhou, Weiguan; Chuang, Chen; et al. (Frontiers in Physiology, 2022)
Medical leeches are widely been used in biochemical and clinical medical studies, helping to restore blood circulation to grafted or severely injured tissue. Mostly, adult leeches are being used in the traditional pharmacopeia, but the gene expression profiling of leeches in different growth periods is not well-reported. So, in this study, we used transcriptome analysis to analyze the comparative gene expression patterns of Hirudinaria manillensis (H. manillensis) in different growth periods, including larval, young, and adult stages. We constructed 24 cDNA libraries from H. manillensis larval, young, and adult stages, and about 54,639,118 sequences were generated, 18,106 mRNA transcripts of which 958 novel mRNAs and 491 lncRNAs were also assembled as well. Furthermore, the results of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses revealed that the differentially upregulated genes from the larval to adult stages were enriched in pathways such as cilium, myofibril, contractile fiber, cytoskeleton proteins, dilated cardiomyopathy, adrenergic signaling in cardiomyocytes, etc. Moreover, in the adult stages, a significant increase in the expression of the Hirudin-HM (HIRM2) genes was detected. In addition, our comparative transcriptome profiling data from different growth stages of H. manillensis also identified a large number of DEGs and DElncRNAs which were tentatively found to be associated with the growth of H. manillensis; as it grew, the muscle-related gene expression increased, while the lipid metabolism and need for stimulation and nutrition-related genes decreased. Similarly, the higher expression of HIRM2 might attribute to the high expression of protein disulfide isomerase gene family (PDI) family genes in adulthood, which provides an important clue that why adult leeches rather than young leeches are widely used in clinical therapeutics and traditional Chinese medicine.